(untitled) (Bulletin of the International Association for Paleodontology, 2025)
ABSTRACT A rare case of bilateral odontogenic maxillary sinusitis associated with advanced tooth abrasion in a female individual from late antiquity Philippopolis is presented and discussed. Keywords: odontogenic maxillary sinusitis; tooth abrasion, late antiquity